Primary School Teachers' Technology Readiness for Artificial Intelligence Integration in Science Learning in Indonesia - Kurniawan, Sasmita; Maryani, Ika (Journal of Educational Technology Innovation and Applications, 2025)
This study explores the readiness of elementary school teachers at Muhammadiyah Primary School in Bantul, Yogyakarta, Indonesia, to integrate Artificial Intelligence (AI) into science education. Utilizing a qualitative descriptive method, the research focuses on the four constructs of the Technology Readiness Index (TRI): Optimism, Innovativeness, Discomfort, and Insecurity. Data were collected through interviews, observations, and documentation involving school principals, vice principals, and Grade IV science teachers. Results reveal high optimism and innovativeness among educators toward using AI tools, such as bright projectors and digital applications, to enhance student engagement and learning effectiveness. However, discomfort and insecurity persist due to limited training and data privacy concerns. The study concludes that comprehensive training and institutional support are essential to foster a safe and efficient integration of AI in primary education.